2023
DOI: 10.3390/pathogens12081048
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Leishmania infantum in Wild Mammals Admitted to Recovery Centers in Spain

Iris Azami-Conesa,
Paula Pérez-Moreno,
Pablo Matas Méndez
et al.

Abstract: Zoonotic leishmaniasis caused by Leishmania infantum is distributed worldwide and affects humans and domestic and wild mammals. In Europe, specifically in the Mediterranean basin, leishmaniasis is endemic due to the concurrence of the phlebotomine vectors and reservoir mammals, including carnivorous wildlife species and other less studied wild species. In this article, spleen, skin, and eye or oral swabs taken from 134 wild mammals admitted to five wildlife recovery centers in Spain were used. PCR employing fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This study reported infection by potentially zoonotic parasites, including Capillaria spp., Acanthocephala, Brachylaima spp., H. erinacei and Trematoda ( Liatis et al, 2017 ). In other studies, hedgehogs were found infected with enteric zoonotic protozoa like Blastocystis sp., Cryptosporidium spp., G. duodenalis ( Gomes-Gonçalves et al, 2024 ) and L. infantum ( Azami-Conesa et al, 2023 ). The encroachment of humans into hedgehog habitats has disrupted the delicate balance of the human-animal-environment interface, further emphasizing the importance of understanding and managing zoonotic risks associated with hedgehog populations.…”
Section: Omnivoresmentioning
confidence: 99%
“…This study reported infection by potentially zoonotic parasites, including Capillaria spp., Acanthocephala, Brachylaima spp., H. erinacei and Trematoda ( Liatis et al, 2017 ). In other studies, hedgehogs were found infected with enteric zoonotic protozoa like Blastocystis sp., Cryptosporidium spp., G. duodenalis ( Gomes-Gonçalves et al, 2024 ) and L. infantum ( Azami-Conesa et al, 2023 ). The encroachment of humans into hedgehog habitats has disrupted the delicate balance of the human-animal-environment interface, further emphasizing the importance of understanding and managing zoonotic risks associated with hedgehog populations.…”
Section: Omnivoresmentioning
confidence: 99%